2012
DOI: 10.1002/term.552
|View full text |Cite
|
Sign up to set email alerts
|

Experimental therapies for repair of the central nervous system: stem cells and tissue engineering

Abstract: Several stem cell-based therapeutic tools are currently being investigated for the regeneration of central nervous system (CNS) injuries. This review focuses on innovative approaches for CNS tissue repair via the use of implantable cellular devices. These devices are supported by biopharmaceuticals and conventional physiotherapy for the restoration of lost neuronal circuits and CNS function. This paper further reviews new and promising tools currently in pre-clinical and clinical tests for the treatment of CNS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 113 publications
0
26
0
1
Order By: Relevance
“…Biodegradable polymer scaffolds can act as a short‐term substitute for the extracellular matrix (ECM) and contribute to the regeneration of damaged tissue (Langer and Vacanti, ). Previous studies have revealed that tissue engineering would be useful to non‐invasively deliver the donor cells to the injured brain (Osanai et al ., ; Yasuda et al ., ; Forraz et al ., ). However, the technique still holds several problems.…”
Section: Introductionmentioning
confidence: 97%
“…Biodegradable polymer scaffolds can act as a short‐term substitute for the extracellular matrix (ECM) and contribute to the regeneration of damaged tissue (Langer and Vacanti, ). Previous studies have revealed that tissue engineering would be useful to non‐invasively deliver the donor cells to the injured brain (Osanai et al ., ; Yasuda et al ., ; Forraz et al ., ). However, the technique still holds several problems.…”
Section: Introductionmentioning
confidence: 97%
“…Cell therapy is promising for repair of the damaged nervous system [13]. Bone marrow stromal cells (BMSCs) are candidate cells for such therapies because of their repair proficiency and relative accessibility [47].…”
Section: Introductionmentioning
confidence: 99%
“…Stem cells transplant is a promising therapy for the repair of damaged nervous system [5][6][7]. Bone marrow derived mesenchymal stem cells (BMSCs) are one of the most commonly used cell to treat injured spinal cord.…”
Section: Introductionmentioning
confidence: 99%